The art of client service : the classic guide - Solomon, Robert (Hoboken, New Jersey : Wiley, 2016)
"A practical guide for providing exceptional client service Most advertising and marketing people would claim great client service is an elusive, ephemeral pursuit, not easily characterized by a precise skill set or inventory of responsibilities; this book and its author argue otherwise, claiming there are definable, actionable methods to the role, and provide guidance designed to achieve more effective work. Written by one of the industry's most knowledgeable client services executives, the book begins with a definition, then follows a path from an initial new business win to beginning, building, losing, then regaining trust with clients. It is a powerful source of counsel for those new to the business, for industry veterans who want to refresh or validate what they know, and for anyone in the middle of the journey to get better at what they do"--Publisher's description.
Includes bibliographical references and index.
What makes great client service? -- Part one: how to be great with clients. Account management's role -- Achieving the next level -- Transforming a career into a calling -- Part two: winning new business for your agency. New business: what it is, why it is important, and why you should give a damn -- How to contribute before, during, and after pitch day -- Getting to yes -- Part three: beginning a client relationship. In a high tech world, be low tech -- What success looks like -- Always manage client expectations from the outset -- Be multilingual -- Live the client's brand -- Ask, "what do my colleagues need to create great advertising?" Then deliver it -- Part four: how to ... run a meeting -- Brief a colleague -- Write a conference report -- Perfect the perfect scope of work -- Craft that schedule you need to create -- Build a better budget -- Draft a letter of proposal -- Create a powerpoint presentation -- Part five: formulating the brief that drives great creative. Take the word brief seriously -- What makes a brilliant brief? -- In writing the brief, provide the client's perspective -- Know when to look it up; know when to make it up -- Part six: establishing trust with clients. Great work wins business; a great relationship keeps it -- Client presentations are as important as new business presentations -- Always ask, "does this advertising pass the 'so what' test?"--Don't fall in love with good work; don't fall for bad work -- Choice is good -- Fight about the work with colleagues; fight for it with clients -- Do not sell -- Bring your clients into the process early and often -- Respect what it takes to do great creative -- Credit is for creative directors -- We are smarter together than we are alone -- Judgment overrides any rule -- Ideas are the currency we trade in -- Part seven: building long-term client relationships. Make no commitment without consultation -- Take on the coloration of your clients; do not compromise your character -- Never forget it's a business -- Once a client, always a client -- Going rogue -- Part eight: how to deal with unhappy clients. Always think endgame -- No surprises about money or time -- Deal with problems head-on -- If things go wrong, take the blame -- What happens when i screw up? -- Getting fired -- Part nine: regaining client trust. How happy clients help you gain new ones -- Five client challenges to agencies -- Five client service principles to believe in -- Acknowledgments: remember to say "thank you" -- Postscript -- Dressing the part -- A bunch of books to make you better at what you do.
Online resource; title from electronic title page (ProQuest Ebook Central, viewed August 29, 2019).
John Wiley and Sons
Keywords: Advertising; Marketing; Customer relations; Marketing; Marketing; marketing; BUSINESS & ECONOMICS -- Customer Relations; Advertising; Customer relations; Marketing